1998
DOI: 10.1103/physrevlett.81.3300
|View full text |Cite
|
Sign up to set email alerts
|

Embrittlement and the Bistable Crystal Structure of Zirconium Hydride

Abstract: Embrittlement and the bistable crystal structure of zirconium hydride -Ackland replies Citation for published version: Ackland, GJ 1998, 'Embrittlement and the bistable crystal structure of zirconium hydride -Ackland replies'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…6,16 Some of these controversies may be ascribed to the fact that conventional laboratory techniques used to study Zr hydride phases are surface techniques, which provide only limited information about the mechanical properties of Zr hydrides in the bulk, and their crystallography and relationship with the α-Zr or Zr-alloys matrix. 19 Although numerous first-principles studies have focused on the structures and electronic properties of α-Zr and Zr hydrides, [20][21][22][23][24][25][26] some discrepancies remain. For example, the H-atom arrangement in the cubic δ-ZrH 1.5 equilibrium phase used by Glazoff et al 25 differs from the one used by Zhu et al 24 and Olsson et al 26 In addition, while in the latter two studies the same model is used for δ-ZrH 1.5 , Zhu et al 24 reported a cubic equilibrium phase and Olsson et al 26 used a tetragonal equilibrium phase.…”
Section: Introductionmentioning
confidence: 99%
“…6,16 Some of these controversies may be ascribed to the fact that conventional laboratory techniques used to study Zr hydride phases are surface techniques, which provide only limited information about the mechanical properties of Zr hydrides in the bulk, and their crystallography and relationship with the α-Zr or Zr-alloys matrix. 19 Although numerous first-principles studies have focused on the structures and electronic properties of α-Zr and Zr hydrides, [20][21][22][23][24][25][26] some discrepancies remain. For example, the H-atom arrangement in the cubic δ-ZrH 1.5 equilibrium phase used by Glazoff et al 25 differs from the one used by Zhu et al 24 and Olsson et al 26 In addition, while in the latter two studies the same model is used for δ-ZrH 1.5 , Zhu et al 24 reported a cubic equilibrium phase and Olsson et al 26 used a tetragonal equilibrium phase.…”
Section: Introductionmentioning
confidence: 99%
“…This double-minimum structure implies that a small stress will lead to a transition between the two structures accompanied by a large strain, a behaviour which plays an important role in understanding the δphase transition for ZrH 2 . Unfortunately, Ackland's density-of-states (DOS) curves are obviously in error (Gupta 1998, Ackland 1998b), but he claims that the other results are not affected.…”
Section: Introductionmentioning
confidence: 99%
“…Before the calculation of the electron-phonon coupling in the Zr-H system, we determinated the lattice structure of this system. The lattice structure of Zr-H systems has been well studied in both experimental and theoretical studies 13,15,20,21,24,25,27,35,50 . In the present work, for zirconium hydrides (with hydrogen concentration x ≥ 1), we studied the stable configurations which were defined in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown in experimental and theoretical works that at low H concentrations, the Zr-H system has a hexagonal close packed (HCP) structure and H atoms are located at tetragonal interstitial sites [20][21][22][23] . At high H concentrations (1 H/Zr 2), the Zr-H system has a face-centered cubic (FCC) or facecentered tetragonal (FCT) structure 15,[24][25][26][27] . The transition from the δ phase (FCC structure) to the ε phase (FCT structure, c < a) was investigated in Refs.…”
Section: Introductionmentioning
confidence: 99%